Green Tourism Village Education: A Public Participation-Based Innovation in Munggangsari Village, Kaliangkrik District, Magelang Regency - Saputro, Iwan Hardi; Arumsari, Nugraheni; Ruhadi, Ruhadi; Kristiono, Natal; Wiwitono, Bambang; Syahidah, Zahra Zilan; Prasetyana, Didi Khomsa (Universitas Negeri Semarang, 2024)
Community service activities in tourism village education were conducted to provide assistance and foster innovations, particularly those based on community participation. The limited involvement of Karang Taruna Sari Muda Manunggal in optimizing the existing tourism potential highlighted the necessity for such activities. Therefore, the community service team organized workshops featuring professional practitioners from Padjer School, an independent organization addressing public issues related to tourism village development. These workshops aimed to enhance community engagement and develop sustainable tourism innovations. The results demonstrated that collaborative participation played a significant role in improving the effectiveness of tourism village development. In conclusion, community assistance involving active public participation was found to accelerate the achievement of sustainable tourism development goals.